P2_9 Feasibility of Outrunning Climate Change - O'Sullivan, Rachael; Carter, Samuel; Lyons, Hannah; Nixon, Josh (Physics Special Topics, 2022)
In this paper we investigate the feasibility of moving the Earth away from the Sun to combat climate change. We found that the energy needed to move the Earth 5.44 × 106 m is 8.71 × 1030 J per year for the lower bound and 5.29 × 1033 J to move it 1.31 × 108 J for the upper bound. For the lower bound, the number of rockets required to generate this energy is 1.21 × 1030 and would cost 4.97 × 1039 USD. For the upper bound, 1.77 × 1034 rockets would be needed, costing 7.26 × 1043 USD. We conclude that this is not a feasible method for combating climate change as using renewable energy sources to power the entire planet would be much more cost effective.